Pengaplikasian Seni Kaligrafi Dalam Meningkatkan Maharah Kitabah: Perspektif Sejarah - Abdurrahman Abdurrahman; Arjuna Dwi Maulana; Khairunnisa Khairunnisa; Nayla Khalisa; Siti Nadiyyana; Sahkholid Nasution (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2024)
Writing calligraphy with Islamic culture cannot be eliminated because every civilization will leave behind something that can be learned from and developed, so that calligraphy becomes an art that has a long history for Islamic civilization and culture.calligraphy as an Islamic art is the most important aspect of Islamic science, the Arabic Al-Qur’an is an obligation to study Arabic grammar. One of the skills in Arabic Grammar according ti the rules, both in terms of length, short in the from of latters to be stylish and beautiful. The method used in this research is literature study, which is a method used in research aimed attt collecting data by talking data from library studies and including relevant research in journals as research material The word calligraphy comes from the Latin kalios (calios) which means beautiful graf (grafh) which means drawing and writing in English. Calligraphy is known as calligraphy which means the art of beautiful writing. Calligraphy writing with Islamic culture cannot be eliminated because every civilization will leave something behind. Lessons can be learned and developed, so that calligraphy becomes an art that has a long history of Islamic civilization and culture.